Enter the middleman: Legitimisation of literary agents in the British Victorian publishing industry 1875–1900. Issue 6 (17th August 2020) - Joseph, Marrisa
Abstract: The literary agent is a recent addition to the publishing industry, yet in a relatively short space of time has become instrumental in the production of literature. This article examines the origins and development of the A.P. Watt literary agency to explore how it became a dominant organisation in the late nineteenth century. It analyses how its founder Alexander Pollock Watt, despite being met with resistance, gained legitimacy to be accepted by authors and publishers. Through an analysis of historical sources this article argues that by using contract law, Watt was able to disrupt existing business practices.